2015
DOI: 10.1523/jneurosci.0129-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Saccades and Perceived Size after Trans-Saccadic Changes of Object Size

Abstract: When saccadic eye movements consistently fail to land on the intended target, saccade accuracy is maintained by gradually adapting the amplitude of successive saccades to the same target. Such saccadic adaptation is usually induced by systematically displacing a small visual target during the execution of the saccade. However, saccades are normally performed to extended objects. Here we report changes in saccade amplitude when the size of a target object is systematically changed during a saccade. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 38 publications
4
67
0
Order By: Relevance
“…However, it is currently unclear whether the presaccadic visual input is stored or that a prediction of postsaccadic visual input is made and stored prior to the saccade. Several studies on transsaccadic learning have, by inducing changes to saccade targets during the saccade, shown that observers could be taught to associate different presaccadic images with postsaccadic visual input (Bosco et al, 2015;Herwig et al, 2015;Valsecchi & Gegenfurtner, 2016). These studies provide evidence for the account that what was stored in VWM is, at least partly, a prediction of upcoming retinal input.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, it is currently unclear whether the presaccadic visual input is stored or that a prediction of postsaccadic visual input is made and stored prior to the saccade. Several studies on transsaccadic learning have, by inducing changes to saccade targets during the saccade, shown that observers could be taught to associate different presaccadic images with postsaccadic visual input (Bosco et al, 2015;Herwig et al, 2015;Valsecchi & Gegenfurtner, 2016). These studies provide evidence for the account that what was stored in VWM is, at least partly, a prediction of upcoming retinal input.…”
Section: Discussionmentioning
confidence: 80%
“…For example, after the saccade has been completed, the postsaccadic visual input can be integrated with the visual input stored in VWM to estimate saccade accuracy and increase the precision of information that is processed by the visual system (Ganmor, Landy, & Simoncelli, 2015;Oostwoud Wijdenes, Marshall, & Bays, 2015;Wolf & Schütz, 2015). Other possible mechanisms include transsaccadic learning, as several authors have shown that transsaccadic changes of stimuli (e.g., shape and spatial frequency) can alter how observers respond to presaccadic retinal stimuli (Bosco, Lappe, & Fattori, 2015;Herwig, Weiß, & Schneider, 2015;Valsecchi & Gegenfurtner, 2016). Transsaccadic learning is thought to occur because the visual system learns to associate presaccadic peripheral visual input and postsaccadic foveal visual input over the course of many saccades (Weiß, Schneider, & Herwig, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In our daily life we continuously move our gaze toward objects that we want to scrutinize, and one could argue that the main function of peripheral vision is to guide foveal selection rather than to support perception. Albeit speculative, one alternative way of looking at this phenomenon is to consider it one result of the predictive mechanisms that supplement the impoverished representation of our peripheral visual field, along with foveal-to-peripheral extrapolation (Otten et al, 2016;Toscani et al, 2017) and transsaccadic learning (Bosco et al, 2015;Herwig, 2015;Herwig et al, 2015;Valsecchi & Gegenfurtner, 2016;Weiß et al, 2014). The predictive nature of peripheral vision might subsume other phenomena such as the tendency to show liberal criteria for detecting peripheral targets (Solovey, Graney, & Lau, 2015) and the tendency to be overconfident in peripheral perceptual judgments (Li, Lau, & Odegaard, 2018;Odegaard, Chang, Lau, & Cheung, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible to assume that the tendency to perceive sharp and straight edges in the periphery originates in our experience of foveal vision. We know that peripheral appearance can be influenced by learned associations between peripheral and foveal stimulation (Bosco et al, 2015;Herwig et al, 2015;Valsecchi & Gegenfurtner, 2016). Nonetheless, specific experiments will be needed to prove that this is the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation